Role of Granulocyte-colony Stimulating Factor in the Protection of Cerebral Vascular Endothelium, White Matter, and Cognition - Tuo, Minghui; Xiao, Yunyue; Xu, Yan; Wang, Lisha; Wei, Xin; Zhang, Lei (Current Neurovascular Research, 2019)
Background: Granulocyte-colony stimulating factor (G-CSF) has protective effects on many neurological diseases. The effects of G-CSF on vascular endothelium and White Matter (WM) injury in Cerebral Small Vessel Disease (CSVD) were explored in this study via a model of spontaneously hypertensive rat (SHR) in order to elucidate the mechanism of G-CSF in Vascular Cognitive Impairment (VCI). Methods: 24-week-old male SHRs were randomly divided into the treatment group and model group, with the same age Wistar rats as the control group. The novel object recognition test (NORT) and Morris water maze were conducted after 7 days of G-CSF(50ug/kg) or normal saline treatment to examine their non-spatial and spatial cognitive functions. After that, a transmission electron microscope (TEM) and FLB staining were used to observe the vascular endothelial cell and WM damage. Furthermore, the expression of VEGF, MMP-9, Caspase-3, TUNEL and BrdULaminin in the cortical area was detected by immunostaining methods. Results: Our results showed that G-CSF promoted the expression of VEGF and BrdU+-Laminin+ endothelial cells, but down-regulated the level of MMP-9, thus significantly repaired the cerebral vascular endothelial cells and perivascular structure in SHR. The WM damage, the expression of caspase-3 and the apoptosis rate decreased after G-CSF treatment. Ultimately, G-CSF improved the non-spatial cognitive function in SHR rather than the spatial cognitive function. Conclusion: Therefore, our findings indicated that G-CSF might facilitate the improvement of non-spatial cognitive function in CSVD by repairing endothelial cells and alleviating WM damage.
Keywords: cognitive